Killer looks: the forgotten history of plastic surgery in prisons - Stone, Zara (Prometheus Books, 2021)
"In this highly original and highly researched book, Zara Stone draws on the intersectionality of socioeconomic success, racial bias, the prison industry complex, and the fallacy of attractiveness to get to the heart of how appearance and societal approval creates self-worth, and uncovers deeper truths of beauty bias, inherited racism, effective recidivism programs, and inequality"--